A systematic review and Bayesian network meta-analysis on the effect of different anticoagulants on the prophylaxis of post-thrombotic syndrome after deep venous thrombosis - Shao, Jingbo; Zhou, Qianwen; Jin, Fukang; Reißfelder, Christoph; Sigl, Martin; Yagublu, Vugar; Keese, Michael (Journal of Clinical Medicine, 2023)
Background: Postthrombotic syndrome (PTS) has a major impact on the quality of life after deep venous thrombosis (DVT). From clinical practice and related trials, anticoagulants show potential for reducing the occurrence and alleviating the symptoms of PTS. Methods: A systematic review and Bayesian network meta-analysis (NMA) were conducted by combing the literature from the databases of MEDLINE, Embase, Web of Science, Cochrane Libraries, and ClinicalTrials, through a variety of medical subject headings (Mesh) and PTS keywords. With regard to PTS prophylaxis, all anticoagulant-related randomized controlled trials (RCTs) and observational studies were assessed. The network model was conducted through the R software, and further comparisons were conducted using the Bayesian hierarchical random effects model. The odds ratio (OR) and the corresponding 95% CI were calculated for analysis. Results: Data from two RCTs and nine non-randomized studies meeting the selection criteria were included in the Bayesian analysis model, which incorporated seven anticoagulants. Edoxaban (OR: 0.42, 95% CI: 0.18-1.0) and rivaroxaban (OR: 0.54, 95% CI: 0.38-0.76) were significantly more effective than warfarin in the prevention of PTS (Villalta score ≥ 5). A subgroup analysis based on the severity of PTS showed that rivaroxaban was more effective than warfarin, with OR: 0.59, 95% CI: 0.41-0.84 (Villalta score 5 to 14) and OR: 0.48, 95% CI: 0.22-0.9 (Villalta score ≥ 15, ulceration), respectively. Edoxaban had the highest probability (80.1%) of providing preventive benefits for PTS. For mild/moderate and severe PTS, rivaroxaban provided the highest benefits in preventing PTS (89.3% and 85.6%, respectively). Conclusion: Edoxaban demonstrated a better prophylactic effect on PTS (Villalta score > 5), while rivaroxaban displayed a better effect against mild/moderate (Villalta score 5 to 14) and severe PTS (Villalta score ≥ 15, ulceration).